Stress-based vs.syllable-based languages: perception of timing differences in English and Croatian - Josipović, Višnja (Array, 1991)
The construct of isochrony in stress-based languages was tested utilizing an aural-perceptual task contrasting English and Croatian. Native speakers were asked to compare the durations of interstress intervals between languages. Statistical analyses revealed that native language was not the factor in listener performance. While no consistent error type emerged, auditors tended to judge the first item in the pair as being greater than or equal to the second. These results are discussed with respect to the relationship between syllable structure and stress in these languages.